1995
DOI: 10.2166/wst.1995.0033
|View full text |Cite
|
Sign up to set email alerts
|

A stochastic approach to designing wetlands for stormwater pollution control

Abstract: Central to wetland design for stormwater pollution management is the proper control of the hydrologic regime of these wetlands and wet detention basins. The paper proposes a stochastic approach in determining the appropriate wetland size for stormwater treatment in recognition of the inherent variability of stormwater runoff and pollutant load generation within a storm event and between storm event. The determination of wetland size would include the use of stochastic generation of stormwater runoff and contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…In some cases this is impossible due to lack of space, or unnecessary due to small amplitudes of flow peaks, but it should at least be considered. The term "hydrological effectiveness", introduced by Wong and Somes (1995), describes this aspect, and is defined as the ratio between the volume entering the pond and the total volume of runoff. The second aspect is to capture and retain flow peaks, which demands a retention volume.…”
Section: Impacts Of Variable Hydrological Loadmentioning
confidence: 99%
“…In some cases this is impossible due to lack of space, or unnecessary due to small amplitudes of flow peaks, but it should at least be considered. The term "hydrological effectiveness", introduced by Wong and Somes (1995), describes this aspect, and is defined as the ratio between the volume entering the pond and the total volume of runoff. The second aspect is to capture and retain flow peaks, which demands a retention volume.…”
Section: Impacts Of Variable Hydrological Loadmentioning
confidence: 99%
“…Hydraulic eciency can be described as how well the incoming water distributes within the pond (Wong & Somes, 1995). All of the design models in current use assume uniform¯ow conditions and unrestricted opportunities for contact between the incoming water and the organisms responsible for treatment.…”
Section: Hydraulic Performance and Eciency: A Theoretical Backgroundmentioning
confidence: 99%
“…Several authors have indicated that nutrient removal performance is governed by hydraulic efficiency (how well the water distributes throughout the system) with optimum efficiency described as a uniform velocity profile (e.g. plug flow; Wong and Somes 1995;Walker 1998;Persson et al 1999;Persson 2000). Walker (1998) studied wetland basins with various length to width ratios and concluded that basins with low length to width rations (0.5:1) resulted in poor residence time and basins with length to width ratio greater than 4:1 resulted in performance similar to plug flow.…”
Section: Literaturementioning
confidence: 99%